2009
DOI: 10.1111/j.1423-0410.2009.01221.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial screening of platelet concentrates: results of 2 years active surveillance of transfused positive cultured units released as negative to date

Abstract: Two of 158 transfusions of PCs released as 'negative to date', but with a confirmed positive BacT/ALERT result, were initially associated with transfusion reactions. However, the imputability of both reactions was low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 7 publications
1
36
0
Order By: Relevance
“…The analytical sensitivity was determined in several studies and was found to be less than 1 colony forming unit (CFU)/ml [9][10][11][12][13][14]. The culture methods were used in combination with a 'negative-to-date' concept [15][16][17][18]. All of the samples were collected from the platelet concentrates within 24 h after donation.…”
Section: Culture Methods In Combination With a 'Negative-to-date' Conmentioning
confidence: 99%
“…The analytical sensitivity was determined in several studies and was found to be less than 1 colony forming unit (CFU)/ml [9][10][11][12][13][14]. The culture methods were used in combination with a 'negative-to-date' concept [15][16][17][18]. All of the samples were collected from the platelet concentrates within 24 h after donation.…”
Section: Culture Methods In Combination With a 'Negative-to-date' Conmentioning
confidence: 99%
“…Fifteen initial positive PCs cultures could not be confirmed by reculturing of the positive BacT/Alert bottle. Two of these were already transfused but neither was involved in a transfusion reaction nor the septic period (Koopman et al, 2009). …”
Section: Strain As Identified By Sequencing Identification Confidencementioning
confidence: 99%
“…Many countries have implemented automated culture systems using the negative-to-date concept to screen PCs for bacterial contamination [13,20,21,22,23]. Cultivation or incubation methods require time for signal production as they depend on microbial growth.…”
Section: Diagnostic Methods - Bacterial Screening Strategiesmentioning
confidence: 99%